(untitled) (Research, Society and Development, 2023)
The diseases and injuries caused by the presence of ticks in cattle have been an obstacle for dairy farming, since there are great economic losses for producers. Control methods for these arachnids are ways to avoid this problem. However, with the rampant and inadequate use of chemical products, some producers and the scientific community noticed the emergence of tick resistance to most available products, environmental contamination and the need to adapt to the increasingly demanding consumer market. Therefore, the search for a low-cost way to control ticks was necessary. The study was carried out on a farm in Ingaí, in the south of MG, from October 2022 to April 2023. The effectiveness of using homeopathy provided with mineral salt, made on the property, to control ticks in cattle was evaluated. For this, 20 animals of the Girolando and Holstein breeds raised in a pasture system were analyzed. The animals were divided into 2 groups (n=10 in each), one receiving treatment with homeopathy and the other with a commercial product based on cypermethrin pour on. During the period of this study, the main lesions and conditions caused by ticks and the density of their presence in the animals were identified and characterized. After analyzing these data, it was possible to understand the effectiveness of using homeopathy manufactured on the property as a control of the tick population in dairy cattle.